2020
DOI: 10.1111/nicc.12577
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' and physicians' knowledge of guidelines for preventing catheter‐related blood stream infections

Abstract: Background: Catheter-related blood stream infection (CRBSI) is considered a major challenge for health care providers working in intensive care units.Aim: This study aimed to evaluate and compare the knowledge of evidence-based guidelines for preventing catheter-related blood Stream infections among physicians and nurses working in critical care units in Jordan.Design: A cross-sectional survey design was utilized. Methods:The study was conducted in five intensive care units; 181 nurses and 68 physicians were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 35 publications
1
20
2
Order By: Relevance
“…The better knowledge of infection control and prevention rules among nurses than physicians was also confirmed by other authors. Al Qadire M et al confirmed this phenomenon with regard to procedures related to the prevention of catheterrelated bloodstream infections [14], and Chang et al confirmed it in regard to hand hygiene compliance at critical points of care [15]. An unsatisfactory level of physicians' knowledge of hand hygiene was reported also by Wałaszek et al in a questionnaire study at another teaching hospital in the south of Poland [16].…”
Section: Discussionmentioning
confidence: 84%
“…The better knowledge of infection control and prevention rules among nurses than physicians was also confirmed by other authors. Al Qadire M et al confirmed this phenomenon with regard to procedures related to the prevention of catheterrelated bloodstream infections [14], and Chang et al confirmed it in regard to hand hygiene compliance at critical points of care [15]. An unsatisfactory level of physicians' knowledge of hand hygiene was reported also by Wałaszek et al in a questionnaire study at another teaching hospital in the south of Poland [16].…”
Section: Discussionmentioning
confidence: 84%
“…They are the ones who provide constant care to patients and play a vital role in the care and maintenance of vascular catheters, which explains why they have shown much better knowledge in this area than physicians. However, even this knowledge is insufficient and needs to be standardized [ 4 , 6 , 7 ]. Studies have shown that systematic, brief training of nursing staff increases their knowledge and thus reduces the incidence of CLABSI [ 17 ] by up to 41.7% [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous surveys of knowledge on central-line-associated bloodstream infections (CLABSIs) involving both physicians and nurses show that nurses are more knowledgeable in this area [ 4 , 6 , 7 , 8 ]. On the other hand, their knowledge is unstructured.…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (2017) reported that ~30% of nosocomial hospital infections are due to catheter-associated bloodstream infections (CRBSI). In addition, more than half of bloodstream infections are caused by CRBSI which increases morbidity and mortality rates and increases healthcare costs ( Tatsuno et al, 2019;Despotovic et al,.2020; Al Qadire & Hani, 2022).…”
Section: Introductionmentioning
confidence: 99%